Political Influence on Judicial Intervention - Sitthisak, Chirawan; Potiwan, Piyaluk; Bamroongboon, Kittikorn (Journal for Developing the Social and Community, 2021)
The study of political influence on judicial intervention aims to study the styles and methods of using political influence to intervene in the judicial process of government officials. This study is a qualitative research, the target group used in the study consists of police officer government officials under the prosecutor’s office, civil servants under the courts of justice and civil servants of the department of corrections a total of 60 people, using observation methods and interviewing methods as tools. Data analysis was by content synthesis and data validation by triangulation method. The result founded; in result of the first aspect, the reasons why all governments wanted to interfere judicial process were because they wanted to use power to protect the interests of themselves and their followers including to lay the foundation for power use judicial as a tool to convince people to agree with the government, and prevent mass citizen in challenging the government’s power. In the second aspect, in the past the government politicians interference judicial process by legal direct, The conformation of intervention that the government uses depends largely on the political and administrative context, that is, if it is the era of the military government or the revolutionary era of the coup, the type of intervention will be in the form of state power through law, but if a democratic government is open to the economy, the intervention model will be very complicated by using both state power and capital power.